EKSPLORASI KEMAMPUAN PEMECAHAN MASALAH MATEMATIS MAHASISWA PENDIDIKAN GURU SEKOLAH DASAR - Nelly Rhosyida (Science Tech: Jurnal Ilmu Pengetahuan dan Teknologi, 2017)
This study is aimed to explore the achievement of mathematical probem solving skill of student in PGSD Sarjanawiyata Tamansiswa University, and student’s mistake on mathematical problem solving test.This study is a qualitative research and case studies. The subjects were students of the University of Sarjanawiyata Tamansiswa PGSD Yogyakarta who have following courses Mathematics Learning Problems in Elementary School. Two classes were randomly selected two as a research subject, the classes C and G. The instrument in this research is a problem solving skill testand interview guidelines. Based on test data KPM then conducted interviews to 11 students.The results showed that the mathematical problem solving skill of students PGSD UST is low. It can be seen from the acquisition of the average class, class C and class G, both of them are in the category low (<68), ie 52.3261 and 55.2340. The percentage of the number of students who are in low category in class C is 95.65%, while class G is also quite large at 87.23%. Only a small proportion of students in the midle category. No one in the high category. Most of the student are in understanding of the problem level (65.12%), followed by the strategic planning (46.93%), carry out the completion strategy (32.08%), and the least is the stage of the re-examination (7.7%) , Mistakes made by students on problem solving skill test are incorrect data, the response level conflict, the problem of hierarchy of skills, the procedure is not appropriate, and the missing conclusion